Analisa Kelayakan Finansial Pembangunan Pabrik Briket Tempurung Kelapa Oleh PT. Adibakti Perkasa Indonesia Untuk Memenuhi Pasar Ekspor - Ana Noor Maulana; Dedy Setyo Oetomo; Rizki Fajar Ramdhani (Journal of Management and Industrial Engineering (JMIE), 2024)
PT Adibakti Perkasa Indonesia is a company operating in the MSME sector which produces charcoalbriquette products. In the process of making briquettes, the main raw materials are: coconut shellcharcoal and aci flour as adhesive. This research was conducted to analyze the financial feasibilityof building a new factory (Plant 2) with a production capacity greater than the old factory. based onMarket Aspects, Technical and Production Aspects, as well as Financial Aspects. Based on theresults of data processing, the results obtained are that the company's production capacity forbriquette products is an average of 2100 tons per year, the need for direct labor is 21 employees andindirect employees are 16 employees. Obtained a total investment of Rp. 1,210,025,000, net presentvalue of Rp. 24,268,056.03,- and an internal rate of return of 62%. With a net present value of Rp.24,268,056.03,- ≥ 0 and internal rate of return 62% ≥ MARR, then the investment is declaredfeasible.